Peace and the Transcendentals: The Case of Thomas Aquinas - Meinert, John (European journal for the study of Thomas Aquinas, 2019)
In both the 20th and 21st centuries, there has been a lively debate concerning beauty's transcendental status in Aquinas' thought. Nobody, however, has noticed that this debate can be replicated with peace. Peace's place vis-à-vis the transcendentals is also ambiguous. This paper argues that peace is not an independent transcendental, but a transcendental of the good. In peace's positive and negative rationes, union/order and rest/tranquility, it is reduced to the transcendental good. Yet through this reduction, peace adds conceptual content to ens. Inasmuch as something is, it is ordered/in union. Inasmuch as something is, it is at rest/tranquil.